-36-12x=48

Simple and best practice solution for -36-12x=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36-12x=48 equation:


Simplifying
-36 + -12x = 48

Solving
-36 + -12x = 48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + -12x = 48 + 36

Combine like terms: -36 + 36 = 0
0 + -12x = 48 + 36
-12x = 48 + 36

Combine like terms: 48 + 36 = 84
-12x = 84

Divide each side by '-12'.
x = -7

Simplifying
x = -7

See similar equations:

| 3-(5x+7)=17-8x | | 3(x+45)=2(x+40)+(2x) | | -6-9x+1=7x | | -2y+4x=-4 | | 4x-3(4x+21)=-143 | | -6-9+1=7x | | 4(d+50)=114 | | x^7+x^5+5=0 | | 10a-2ab= | | 8/x=-9 | | 7x+9y=192 | | 50x-80=70x+30 | | 4y+6(-2)y=10 | | 2(-4x+12)=144 | | 1.5(4-w)=-(1.5-8) | | 2logx-log(x+9)-log(x-9)=0 | | 4x=(2x+10) | | y-9=-5/7x | | 5x/2-3=-1 | | X-1/8=-10 | | 5x-2x+7-x=3x+4 | | x/2-9=19 | | 2logx+log(x+9)-log(x-9)=1 | | 10y-8=2 | | 5x-2x+7-x=5x+2 | | 3(2n-3)=5(n+1) | | -3x-3(2x-14)=-66 | | 5x-2x+7-x=7x+4 | | 8.2-4.4= | | 10=-2a-8a | | 5x-2x+7-x=6x+9 | | 5x-2x+7-x=9x+8 |

Equations solver categories